The multiverse of the city: Typology of semantic spaces - Sakharova, Anna (project baikal, 2024)
When we talk about the social, cognitive or discursive space of the city, we use a metaphorical transfer of our ideas about physical space to the ‘semantic’ level. Our internalized ideas about physical space become the basis for such structuring: based on these ideas, we create scientific metalanguages that allow us to discuss social or discursive aspects of urban life. In this paper, we strive to study the cognitive foundations of such metaphorical transfer in more depth, as well as to explore the interrelationships between different types of “semantic” urban spaces.